STUDY OF STUDENTS' ENTREPRENEURSHIP INTEREST AS AN INDICATOR OF OPPORTUNITY FOR ESTABLISHING BUSINESS INCUBATORS IN LOMBOK TOURISM POLYTECHNIC - Yahyadin, Muh.; Hanafi, Hamsu; Sianipar, Christina; Putra, Anak Agung Ngurah Sedana; Mandra, Mandra; Zaki, Lalu Ahmad (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2023)
This research was conducted with the aim of (1) providing an overview of student entrepreneurship interest as an indicator of the opportunity to establish a business incubator at the Lombok Tourism Polytechnic and (2) contributing ideas and enriching the field of tourism business incubator studies and as input and a reference for other research. (3) are used as information and input for stakeholders in developing entrepreneurship. This study used primary data in the form of a questionnaire for as many as 63 students consisting of 4 study programs; 19 students from the room division, seven students from culinary arts, 27 students from food & beverage service, and ten students from travel arrangements, the research was conducted from April to October 2021. Data collection techniques were purposive sampling, and data analysis techniques were descriptive of responses. The respondent gave them in the Questionnaire. The results of this study indicate that: (1) Flexibility, indicating the intention of respondents, 22% strongly agree (2) Innovation, indicating the intention of respondents, 44% strongly agree (3) Social Prestige, showing the respondent's intention in entrepreneurship by 48% strongly agrees (4) Personal challenge, shows the respondent's intention of 60% strongly agrees (5) Leadership, shows the respondent's intention of 45% agrees about leadership (6)Advantage, shows the respondent's intention by 51% strongly agree (7) Being a boss, indicating the intention of respondents by 36% strongly agree.